Changement climatique et dynamique géomorphologique des côtes bretonnes. Leçons pour une gestion responsable de l’imbrication des échelles spatio-temporelles - Alain Hénaff; Catherine Meur-Ferec; Yannick Lageat (Cybergeo)
In France, the strong storms of the last decades and their impacts on coasts has led to emphasize the relationships which may exist between climate change and coastal erosion and flooding. It seems however necessary to consider the contemporaneous geomorphological dynamics of the coasts in the context of their evolution depending upon numerous factors such as the Flandrian transgression, the marine and climate weather, the sedimentary budget and human impacts. Some examples of coastal evolution in Brittany remind us that the shoreline mobility results from processes acting at various scales of time and space. In that context, the predictable impacts of climate change could act as an aggravating factor in an already very unfavorable situation reinforced by the stakes growth.